Protective effects of polyamines on regulation of senescence in spray carnation cut flowers (Dianthus caryophyllus’Spotlight’) - Mahnaz KARIMI; Fateme AKBARI; Ayoub HEIDARZADE (Acta Agriculturae Slovenica)
This study was conducted to evaluate the effect of three polyamines (PAs) on antioxidants capacity, free radical scavenging and vase life improvement of spray carnation cut flowers. Hence, the cut flowers were dipped in different concentrations (0, 1, 2 and 3 mmol) of putrescine (Put), spermidine (Spd) and spermine (Spm) for 24 h. After treatment, the cut flowers were placed in distilled water and kept at 20 °C ± 2 °C, 70-80 % RH. All concentrations of Put treatment improved the vase life of cut spray carnation flowers as compared to control. The highest positive influence on vase life (with 13 days) was related to 2 mmol Put treatments. Result showed that applying Put and Spm treatments at 1 or 2 mmol concentration significantly minimized the percentage of mass loss compared to the control. A significant inhibition of anthocyanin degradation was observed with Put 1 or 2 mmol and Spm 1 mmol Significantly higher activities of catalase and DPPH radical scavenging activity were observed in petals when cut carnations were treated with 1 mmol Put. It can be concluded that application of polyamines such as putrescine can play a key role to prevent or delay deterioration in cut flowers.